Effect of Garlic (Allium sativum) Extract on Recovery and Conception Rate in Infectious Repeat Breeder Crossbred Cows - Bhardwaj, Anvil; Nema, SP; Mahour, SS; Chabra, Daljeet; Rajput, N; Sudarshan, K (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was undertaken to evaluate the therapeutic efficacy of Garlic (Allium sativum) extract in 20 infectious repeat breeder crossbred cows. Animals were divided into two groups of ten in each. The animals in first group were treated intrauterine with 30 ml 15% Garlic extract w/v dissolved in saline at 24 hrs interval for 7 days, while the animals in control group were infused with 30 ml saline for 7 days. Bacterial count in uterine flushing declined significantly (p
Keywords: Repeat breeder; uterine flushing; Garlic extract; bacterial count; PMNs%; Whiteside test; Conception rate